Broadband mesoscopic optoacoustic tomography reveals skin layers - Aguirre, Juan; Schwarz, Mathias; Soliman, Dominik; Buehler, Andreas; Omar, Murad; Ntziachristos, Vasilis (Optics Letters, 2014)
We have imaged for the first time to our knowledge human skin in vivo with a raster-scan optoacoustic mesoscopy system based on a spherically focused transducer with a central frequency of 102.8 MHz and large bandwidth (relative bandwidth 105%). Using tissue phantoms we have studied the ability of the system to image vessels of sizes within the anatomically significant range from the key anatomical vasculature sites. The reconstructed images from experiments in vivo show several structures from the capillary loops at the dermal papillae, the horizontal plexus, and the difference between the dermis and the epidermis layers.
CRIS-Team Scopus Importer:2023-03-08